A Multi-step Intelligent Genetic Algorithm to Optimize Delivery Problem within Interactive-time - ONOYAMA, Takashi; TSURUTA, Setsuo; KUBOTA, Sen; SAKURAI, Yoshitaka (Journal of Japan Society for Fuzzy Theory and Intelligent Informatics, 2008)
To optimize large-scale distribution networks, solving about 1000 (around 40 cities) TSPs (Traveling Salesman Problems) within an interactive length of time (max. scores of seconds) is required. Yet, expert-level (less than 3% of errors) accuracy is necessary. To realize the above requirements, a Multi-step intelligent GA method was developed. This method combines a high-speed GA with an intelligent GA holding problem-oriented knowledge that is effective for some special location patterns. If conventional methods were applied, solutions for more than 20 out of 20,000 cases were below expert-level accuracy. However, the developed method could solve all of 20,000 cases at expert-level.